IMPLEMENTATION EVALUATION OF SAFETY AND HEALTH IN CONSTRUCTION SERVICES IN NORTH SULAWESI - Pingkan Pratasis; Ludfi Djakfar; M. Ruslin Anwar (Journal of Civil Engineering, 2011)
Implementation of OHS management system by construction companies in North Sulawesi has many problems. These problems are identified as inhibiting factors. This study aims to identify inhibiting factors that influence OHS implementation on construction company and how public policy alternatives that can be proposed. Product moment correlation analysis results showed overall effect of those factors, of which the most influential factor is budgetary project planning. Proposed Public policy are: procurement of equipment and materials budget should be included in Cost Expense Plan for construction works; monitoring mechanisms need to be regulated in order to create awareness OHS implementation, including governing authority to the field of OHS in related agencies. Similarly, the rules of reward and punishment to promote awareness of OHS implementation, OHS socialization also be performed periodically, with various forms and methods and direct guidance in the field, establishment of OHS tools and materials management unit.